Mothers, boorais and special care : an exploration of indigenous health care workers' perceptions of the obstetric and neonatal needs in rural Victorian Aboriginal and Torres Strait Islander families transferred to the Mercy Hospital for Women - Middleton, K. Jane.; Onemda VicHealth Koori Health Unit. ([Melbourne] : Onemda Vic Health Koori Health Unit, 2006)
An exploration of Indigenous health care workers' perceptions of obstetric and neo-natal needs of rural Victorian Aboriginal and Torres Strait Islander families transferred to the Mercy Hospital for Women.
"October 2006"
Spiral binding.
Includes bibliographical references (p. 27-29)
Also available in an electronic version on the Internet. Address as of 1/6/07: http://www.onemda.unimelb.edu.au/docs/dP15.pdf.
Keywords: Mercy Hospital for Women (Melbourne, Vic.); Women, Aboriginal Australian -- Medical care -- Victoria; Pregnant women -- Medical care -- Victoria; Rural health services -- Victoria; Health status - Womens health - Maternal health; Research - Methodology and techniques; Health services - Health workers; Victoria (Vic)